ONLINE AND OFFLINE MARKETING MENTORING AND TRAINING FOR SMEs IN JOYOGRAND MERJOSARI MALANG: Promotion, Promotional Media,Product Catalog - Umi Khabibah Umi; Pudji Herijanto; Fullchis Nurtjahjani; Nurdjizah Nurdjizah; Lilies Nur Aini (P3M Politeknik Negeri Malang, 2024)
Assistance and training for SMEs in RW 8 Joyogrand Merjosari Malang Housing is a collaboration with the world of education. This is because there is a need for knowledge about marketing, both online through social media and offline through tools in the form of product catalogs. The catalog displays all the products produced, along with their prices, so this will really help potential consumers in recognizing and knowing what products are produced. The final thing that is hoped for is that a buying and selling transaction will occur between them. If you understand the meaning of promotion, you will know the true purpose of promotion. Not just communication to attract interest or introductions. The aim of promotion is to generate sales from capturing the market, as well as increasing the number of sales, increasing awareness of the sustainability of the buying and selling relationship. The training program for presenting promotional ideas on Facebook/Instagram and the Product Catalog is one of the training programs that can help disseminate product information. Likewise for UKMs in RW 08. They need to open themselves to other people regarding what they produce. By being known by other people, it will increase sales